Inclusiveness of economic growth in Indonesia: the poverty approach - Ahmad Soleh; Suwarni Suwarni (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2023)
Inclusive growth gives a broader concept. The community is not only a beneficiary of growth, but also participates and contributes to the growth process. High economic growth is expected to reduce poverty. The purpose of this study is to analyze inclusive growth in Indonesia. The method used is a descriptive analysis approach. Poverty-Equivalent Growth Rate (PEGR) was developed to measure the coefficient of inclusive growth in Indonesia. The results show that during the period 2001-2020 Indonesia's economic growth has not been inclusive. The inclusive growth coefficient (IGp) is smaller than the economic growth coefficient (Ĝg). This phenomenon also occurred in most provinces and islands during the observation period. High economic growth has not been able to fully reduce poverty. Government strategies and policies that are pro-poor are needed.